EFFECTIVENESS OF OREM SELF-CARE THEORY INTERVENTION FOR IMPROVEMENT IN SELF-CARE PRACTICES AMONG MYOCARDIAL INFARCTION PATIENTS; A QUASI-EXPERIMENTAL STUDY - Sultan, Amir; Khanum, Sabiha (Journal of Postgraduate Medical Institute, 2024)
Objective: The aim of the study was to identify the effectiveness of Orem self-care theory for the improvement of self-care practices among myocardial infarction patients to fill research gap in context of Pakistan. Methodology: The study design was quasi-experimental. The study was conducted between June and September 2022 having a sample size of 90 patients. The study instrument was a self-structured reliable questionnaire of self-care practices that was filled out before intervention and 12 weeks after the intervention, while the intervention was 2 sessions of one hour. Results: In the study, the number of total participants was 90 divided into experimental (n=45) and control group (n=45). In the experimental group majority of the participants were females (51.2%) having a mean score of (61.5 ± 5.5), while in the control group the number of male participants was in majority (57.8%) while the mean score was (61.3 ± 5.1). In experimental group the intervention was effective on physical (p=0.001), psychological (p=0.000), emotional (p=0.009), and spiritual (p=0.003) self-care. While there is no effect seen on workplace and relationship care. Conclusion: The overall self-care of the experimental group was significantly positively changed compared to the control group that concludes that the intervention was effective.